Distributed flood simulation based on satellite rainfall data at the Ciliwung River Basin, Jawa, Indonesia. Issue 1 (1st January 2023) - Sulistyowati, R; Meliani, F; Sapan, E G A; Winarno,; Lestari, S; Hapsari, R I; Cahyaningtiyas, I F; Avianti, E; Eugenie, A; Grace, T; Amaliyah, R; Djoharin, M; et al.
Abstract: Recurrent flooding in Jakarta and surrounding areas due to extreme rainfall is simulated by using distributed hydrological model. In the previous studies, the Rainfall-Runoff Inundation (RRI) model has been used for the flood simulation with 1-km spatial resolution, but it has not been comprehensively investigated. In this paper, extreme rainfall data derived from satellite rainfall data of GSMaP, topography, and land derived from the satellite remote sensing data are used as an input for the RRI model. We analyse the flood simulation at Ciliwung River Basin during 6 (Six) periods of extreme rainfall during January – March 2022 and divide between Flood (F) and Non-Flood (NF) periods. We found that the inundation occurred when the rainfall average reaches more than 7.3 mm/hr and concentrated in the Jakarta downtown area, which had induced the inundation around the Ciliwung river basin.